PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR OPERASI HITUNG BILANGAN CACAH SISWA KELAS IV SDN 102071 DOLOK MASIHUL - Herawati Purba; Syahrial; Lala Jelita Ananda; Apiek Gandamana; Nur Hudayah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low mathematics learning outcomes of fourth-grade students at SDN 102071 Dolok Masihul, particularly in the topic of whole number operations. The learning process, which is still dominated by conventional methods, causes students to be less active, easily bored, and to have a limited understanding of multiplication concepts. Therefore, this study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model based on local wisdom through the traditional game of congklak on students’ learning outcomes. This research employs a quantitative approach with a Pre-Experimental design using a One Group Pretest-Posttest Design. The sample consists of all 29 fourth-grade students, selected using a saturated sampling technique. The instruments used include a learning outcomes test and observation sheets. Data were analyzed using statistical tests to examine the differences between pretest and posttest results. The findings indicate an improvement in students’ learning outcomes after the implementation of the TGT model based on local wisdom. This model enhances student engagement, motivation, and conceptual understanding through interactive and contextual learning. Thus, it can be concluded that the TGT learning model based on local wisdom has a significant effect on students’ learning outcomes in whole number operations.